Ціннісний світ людини в її екзистенції - Подолянко, Л.А. (Наука. Релігія. Суспільство, 2011)
У статті розглядаються сутність і головні характеристики функціонування, динаміки духовно-ціннісних орієнтацій людини, охоплюється велика кількість важливих та взаємопов’язаних питань даного проблемного кола. Наголошується на багатоаспектності феномену духовності. Стверджується, що духовність є атрибутивністю людської суб’єктивності, її втрата перетворює людину на об’єкт. Робиться висновок про те, що людина творить себе самостійно, «вбираючи» ті або інші цінності, завдяки освоєнню та присвоєнню певної системи цінностей. В статье рассматриваются сущность и главные характеристики функционирования, динамики духовно- ценностных ориентаций человека, охватывается большой круг важных и взаимосвязанных вопросов данной проблемной сферы. Делается акцент на многоаспектности феномена духовности. Утверждается, что духовность является атрибутивностью человеческой субъективности, ее утрата превращает человека в объект. Делается вывод о том, что человек создает себя самостоятельно, «вбирая» те или иные ценности, благодаря освоению и присваиванию определенной системы ценностей. It is known that morality of the valued world of a human-being is the variety of energies of the unique essence that exists in the personal world. So the system of values is very important, because the life of a human-being is the endless process of acts of estimation of his/her life as a personality in the society. The reflexive role of values is related to the intellectual life, its world view of self definiteness. It is also important that the existence of a human-beimg means a change of values. For example in boundary situations desires of a human-being to reconsider the base values critically are fully natural. The freedom of actions and personal will enable to carry out concrete acts and to carry responsibility for them. Only in such a case a human-being can exist as a personality with values.